Developing a comprehensive model of Islamic brand personality: a conceptual study - Jan, Muhammad Tahir; Perdana, Firdaus Fanny Putera (Readers Insight Publisher, 2018)
Brand personality plays an important role in affecting customer satisfaction. Muslim population is estimated to reach 30 percent of world’s population and it is considered as the fastest religion spreading in the world. To tap into this market, it is important to explore various aspects of business, in general, and marketing, in particular, from the perspective of Muslim consumers. The present research also attempts to do the same by proposing a conceptual model related to brand personality, named, Islamic Brand Personality (IBP) and its impact on customer satisfaction. Personality dimensions developed by Aaker was extended by undertaking an extensive and exhaustive review of the literature. The same model is revised according to Quran and Hadith. Sophistication and Ruggedness were eliminated during the model development, while other three dimensions, namely, Trustworthiness, Justice and Shariah Compliance emerged during the review. The resulted conceptual model is expected to effectively help the marketers differentiate Islamic brands that eventually can entice more Muslim consumers in using their products compared to the conventional counterparts.